PARTICULAR OTHERS DAN PEER GROUP TEACHING PRIO UTOMO DALAM PROSES MEMOTIVASI PRIA UNTUK BERVASEKTOMI - Dwinda Sekar Andrea; Sri Budi Lestari (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
Family planning is initiated by the government to control birthrate and improve people’s quality of life. It targets both women and men, but in fact there has been an imbalance participation between both genders. The less participation of men and stigmas in the society about vasectomy backgrounds this research. Prio utomo is a community based acceptor supprting group, created by the government, whose mission to motivate, educate and inspire people, so there will be no more stigmas towards vasectomy. This research desscribes how particular others and Prio Utomo in the process of motivation men to do vasectomy. Using case study as a research method, this research took place in Kecamatan Getasan, Kabupaten Semarang, Central Java, Indonesia, where the local Prio Utomo is one of the most successful and active compared to other regions. Analysis result based on Theory of Planned Behavior shows that several informants were motivated by the urge to provide a better life for their family and the raising concern about the wife’s health. More to that, Prio Utomo itself has been motivating men using both personal and interpersonal approach. According to Persuassive Communicaton Theory, motivating activity conducted by Prio Utomo is actually using two dominant appeal that is psychological appeal—in which is achievement motive—and credibility appeal. This research also found the fact that people in Kecamatan Getasan are very heterogeneous and have high level of tolerance. A high tolerance level initiates such an open atmosphere, as of this characteristic don’t allow stigmas to grow and affect people’s decision on family planning. The finding is also a uniqueness for this research. The result of this research shows that Prio Utomo's activities have contributed a significant role in promoting vasectomy. Yet support from government's family planning institution is imperative to ensure the sustainability of this program. Hence during such an awareness and motivation process, the motivator should consider using more interpersonal approach.